Toluene removal from contaminated airborne by using activated carbon / Nur Syuhada' Asmar - Asmar, Nur Syuhada' (Faculty of Applied Sciences, 2009)
This study investigates the reduction of concentration of toluene. Air samples were collected in a small both with 2mx2mx2m dimension. Activated carbon has been used as adsorbent to adsorb the evaporated toluene from the contaminated air. The samples were collected 4 times in every 60 minutes period. Then, all the samples were analyzed by using gas chromatography, GC-FID. The final results indicated that the concentration of toluene reduced from 240.00 mg/m3 to 36.25 mg/m3. The percentage reduction of toluene reaching up to 84%. The concentrations of toluene were below the TWA limit which is 375 mg/m3 (lOOppm).